Place as partner: material and affective intra-play between young people and trees. Issue 2 (4th March 2021) - Goodenough, A.; Waite, S.; Wright, N.
ABSTRACT: A collaboration between the third sector and a university in Southwest England, the Good from Woods project investigated wellbeing outcomes of time spent in woodland through action research by a range of woodland practitioners. The research reported in this article explores relations between children aged 3–15 years and trees in an adventure playground set in woodland regrowth on an old municipal tip. The innovative arts-based methodology highlights playful, imaginative and affective place-based play. We examine the flows of activity amongst human and nonhuman in this environment and consider how this place and its materiality supported intra-play between trees and children, nonhuman and human inhabitants. Our analysis interweaves post-paradigmatic new materialism with ideas of cultureplaces leading us towards an understanding of place as children's (unequal) partner in intra-play.